Export Market Performance of OECD countries: an empirical examination of the role of cost competitiveness - Wendy Carlin; Andrew Glyn; John Van Reenen (Institute for Fiscal Studies (IFS), 1999)
This paper investigates the relationship between export market shares and relative unit labour costs using a long panel of twelve manufacturing industries across fourteen OECD countries. We ask two questions: (a) how sensitive are export market shares to changes in relative costs and (b) what determines the degree of sensitivity? Although both costs and embodied technology are important, we find that neither can fully explain changing export positions. We explore whether the residual country-specific trends might be linked to \~Neep' structural features of economies such as human capital investment and national ownership patterns. On the second question, the sensitivity of exports to labour costs is lower in high tech industries and in core ERM countries. The industry elasticities have increased over time, especially in industries subject to increasing product market competition. We discuss the implications of these findings for European Monetary Union.
Keywords: F1; J3; 330; Export; Lohnstückkosten; Außenhandel mit Industriegütern; Internationaler Wettbewerb; OECD-Staaten